2017
DOI: 10.1002/mp.12489
|View full text |Cite
|
Sign up to set email alerts
|

A Bayesian approach to solve proton stopping powers from noisy multi‐energy CT data

Abstract: The Bayesian ETD is shown to be more robust against noise than similar methods and a promising approach to extract SPR from noisy DECT data. In the advent of commercially available multi-energy CT or photon-counting CT scanners, the Bayesian ETD is expected to allow extracting more information and improve the precision of proton therapy beyond DECT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
70
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 27 publications
(75 citation statements)
references
References 42 publications
3
70
2
Order By: Relevance
“…The standard deviation of the image noise distribution for each energy bin depended on the number of energy bins, σnormalbin=Nbin·σFS, as in Lalonde et al …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The standard deviation of the image noise distribution for each energy bin depended on the number of energy bins, σnormalbin=Nbin·σFS, as in Lalonde et al …”
Section: Methodsmentioning
confidence: 99%
“…have recently proposed new SPR methods for PCD‐CT. Based on computer simulations or multiple regular SECT scans, all three studies found that the root‐mean‐square error (RMSE) for SPR estimation decreased when the number of energy bins increased …”
Section: Introductionmentioning
confidence: 99%
“…The SPR values are calculated from elemental compositions using the Bragg additivity rule as well as the Bethe–Bloch formula. In this study, we investigate an adaptation of this method especially made for SPR prediction from noisy multienergy CT data …”
Section: Methodsmentioning
confidence: 99%
“…For the method of Lalonde et al., we use the measured CT numbers of the phantom to calibrate the Z ‐space coefficients, as proposed in Ref. , eq.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation